Time trends in limited lung function among German middle-aged and older adults - Johannes Beller; Batoul Safieddine; Stefanie Sperlich; Juliane Tetzlaff; Siegfried Geyer (Scientific Reports, 2024)
Abstract Limited lung function represents a serious health impairment. However, studies investigating changes in limited lung function over time are rare. Thus, the current study investigates time-related changes in limited lung function and potential social inequalities. Data from the 2008 and 2017 waves of the population-based German Aging Survey were used in a repeated cross-sectional study design (N = 8778), including participants aged 40 years and older. Lung function was assessed by the peak flow test. Socio-economic indicators included educational attainment, income and occupational group. Additionally, smoking history, occupational exposure to fumes and gases, and physical exercise were used as potentially explanatory variables for the observed changes. We found that the prevalence of limited lung function decreased strongly over time on a descriptive level from 9.0 to 5.4%. In line with these results, a decreasing trend emerged (OR = 0.48) when controlling for age and gender differences. When additionally controlling for changes in socio-economic indicators and explanatory variables there were still significant decreases over time, but the decline was slightly reduced (OR = 0.57). Moreover, similar significant relative decreases over time occurred for middle-aged and older participants, female and male participants, and those belonging to the different socio-economic groups. Thus, limited lung function generally decreased over time. This decrease could partially be explained by beneficial developments in socio-economic indicators, smoking, occupational exposures, and physical exercise. Future studies might investigate how changes in medicinal treatment and prevention efforts have contributed to the observed beneficial trends in lung health.